The Effect of Left-Handed Medical Students on Postural Scoliosis - Gunardi, Santoso; Winata, Handy; Damayanti, Katarina; Padang, Yakin Arung (Jurnal MedScientiae, 2022)
Scoliosis is a deformity abnormality in the spine with the occurrence of deviation of bone segments tothe lateral side with or without accompanied by rotation of the bone that causes the spinal arch.Postural scoliosis is a condition where the curvature of the spine that arises can return to its originalform or is reversible, this often arises because of an incorrect position due to one's habit of activity.In daily life, there are many problems faced by people who are active by using their left hand,especially in adjusting to non-left-handed equipment, such as those with lecture chairs withconnecting tables on the right side which are still very rare or even non-existent on each campus. Theperson who writes using the left hand will make a bad position, the body will bend and slightly rotateto the right to get the elbow so that it can write. With experimental research with one-shoot case studymethod and purposive sampling approach in the active students of the Ukrida Faculty of Medicine in2019 with scoliometer apps pro measurement and The Adam's Forward Bend Test method, it wasfound that writing using the left hand on a lecture chair connected to the table on the right side cansignificantly influence postural scoliosis in the form of an increase in the value of the scoliometer (p= 0,003). This habit will continue to lead to an increase in the degree of curvature of the spine orscoliosis.